Influence of Deep Eutectic Solvent (DES) Pretreatment on Various Chemical Composition of Empty Fruit Bunch (EFB) - Mohd Tajuddin, Aqilah; Harun, Shuhaida; Shaiful Sajab, Mohd; Irwan Zubairi, Saiful; Md Jahim, Jamaliah; Markom, Masturah; Tusirin Mohd Nor, Mohd; Amrin Abdullah, Mohd; Hashim, Norhafizi (International Journal of Engineering and Technology, 2019)
Chemical composition of empty fruit bunch (EFB) is an important chemical property that determines its utilization performance in bioconversion process. Various chemical compositions of EFB have been reported, and these differences in composition affects EFB utilization in terms of conversion and product yield. Complex structure and recalcitrant characteristic of lignocellulosic biomass (LCB) also affects its utilization that leads to pretreatment system requirement. Pretreatment using deep eutectic solvent (DES), a group of ionic liquid (IL), has attracted scientific interest due to its exceptional ability in hemicellulose and lignin removal. This research determined the chemical composition of six native EFB sample collected in Malaysia, and identified composition difference among samples using t-test. The work further determined the influence of DES01 pretreatment on selected pretreated samples using enzymatic hydrolysis process. Chemical compositions of six native EFB samples, collected in Perak, Selangor and Negeri Sembilan in dry and wet seasons, were determined using National Renewable Laboratory Analysis (NREL) protocol. Enzymatic hydrolysis of pretreated EFB samples were conducted following NREL protocol using Cellic CTec2 and Cellic HTec2 enzymes for 72 hours. The t-test analysis on structural carbohydrate (SC) content of native EFB showed Sg. Siput sample (SSD) in dry season and Bahau sample (BW) in wet season had statistically significant difference where native SSD contained the highest SC while native BW had the lowest. Enzymatic hydrolysis results of DES01 SSD and DES01 BW samples indicated the influence of DES01 pretreatment. DES01 SSD substrate produced higher glucan and xylan conversion after 72 hours of hydrolysis with 92.40% and 68.71% respectively compared to the DES01 BW sample with 75.82% and 18.78% only. This could be correlated with higher glucan and lower lignin contents in However, the different composition of native EFB also affected the hydrolysis of pretreated EFB. The variable pressure scanning electron microscopy (VPSEM) analysis showed that EFB structures were destroyed by the hemicellulose and lignin removal after the pretreatment and enzymatic hydrolysis.Â Â